Switch-Related and General Preparation Processes in Task-Switching: Evidence from Multivariate Pattern Classification of EEG Data - Mansfield, Elise L. (J Neurosci, 2012)
The cued-trials task-switching paradigm is used to investigate the processes involved in preparation to change task. Task switch trials typically show poorer performance than task repeat trials, suggesting that additional or more time-consuming preparation processes are required to switch tasks. However, behavioral and neuroimaging studies have so far been unable to decipher whether preparing for a switch in task involves distinct cognitive processes to those required more generally on both switch and repeat trials. The current study addresses this question using a novel multivariate pattern misclassification analysis of frequency band-specific local topographical patterns in human EEG activity that was elicited by cues varying in information value. Within the alpha frequency band, misclassification analysis produced evidence for an early switch-related preparation process over right frontal cortex, as well as a later task readiness preparation process over right parietal cortex. This represents compelling evidence for dissociable switch-related and task readiness preparation processes that show distinct time course and spatial activation patterns.